Efficacy and Safety of Thymoquinone on Suppression of Tumor Growth in N-butyl-N-(4-hydroxybutyl)-Nitrosamine -Induced Bladder Cancer in Rats - Karmand Salih Hamaamin Qadir; Bushra Hassan Marouf (College of Pharmacy University of Baghdad, 2023)
Bladder cancer is one of the most common genitourinary malignancies worldwide, the therapeutic approaches for suppression of urothelial tumor and progression toward distant metastasis are not convincing. The present study was conducted to explore the curative effect and safety of THQ in N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) induced bladder cancer in rat. Twenty-two male Wister albino rats were allocated into three group G1; served as control (n=6) received only the vehicle. G2: carcinogen group (n=6); animals had 0.05% BBN in drinking water for nine weeks. G3: Treatment group (n=10); THQ was administered at a dose of 50mg/Kg/day orally one week prior to the last exposure of BBN and continued till week 20. The bladder wall of all the animals was examined macroscopically for assessment of the number and the surface area of the lesions using Image J software program. Histopathological evaluation was also done for abnormal morphological alterations. Serum was analyzed for measurement of total oxidant status (TOS) and nuclear factor kappa- κB (NF-κB), transforming growth factor beta-1 (TGF-β1) as well as vascular endothelial growth factor (VEGF). Safety of THQ in respect of hematological, liver and renal function were also investigated. Bladder lesions in the THQ-treated group was reduced versus the carcinogen group. Histopathological findings in THQ-treated group demonstrated a significant improvement in the abnormal morphological growth in bladder, the TOS, NF-kβ, TGF-β, VEGF were mitigated non-significantly in the treatment group. The safety profile of THQ showed no significant deleterious effect on hematological, liver and renal function parameters with no signs of toxicity. THQ inhibited the development of neoplastic, preneoplastic transformations and it suppressed premalignant and malignant lesion formation in a rat model of bladder cancer. This might be due to antioxidant and anti-inflammatory properties of THQ. These data suggested that THQ may be effective and safe in ameliorating urinary bladder carcinogenesis.